2009
DOI: 10.1093/pubmed/fdp061
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the provision of elective primary hip and knee replacement: the role of socio-demographic, hospital and distance variables

Abstract: This study found evidence of inequalities in the provision of joint replacement surgery. However, before we can conclude that there is inequity in receipts of healthcare, future research must consider whether these patterns are explained by variations in need across socio-demographic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 29 publications
9
48
1
Order By: Relevance
“…Similar variations were reported for THR ranging from 2.3 to 5.8. Such geographic variation in TJR rates has been also reported in other countries such as Australia [33], the United Kingdom [34], Finland [35], and Germany [36]. These differences, which often remain even after adjusting for age [36], have been attributed to various factors, including a lack of consensus regarding the indications for these procedures [24,32].…”
Section: Discussionmentioning
confidence: 85%
“…Similar variations were reported for THR ranging from 2.3 to 5.8. Such geographic variation in TJR rates has been also reported in other countries such as Australia [33], the United Kingdom [34], Finland [35], and Germany [36]. These differences, which often remain even after adjusting for age [36], have been attributed to various factors, including a lack of consensus regarding the indications for these procedures [24,32].…”
Section: Discussionmentioning
confidence: 85%
“…However, rates of knee replacement per head of population, adjusted for age and sex, vary enormously. For example, a recent study from the UK reported geographical variation across different regions in England, 9 and similar data has been uncovered within Sweden, through its arthroplasty registry 10 . Further analysis of data in England, Sweden, Canada and other countries indicate that inequities exist, with those who are most socio‐economically deprived being the least likely to be operated upon 9–13 .…”
Section: Variations and Inequities In The Provision Of Kjrsmentioning
confidence: 76%
“…In recent decades, limited access to healthcare services has been a problem in many countries (Pomey et al, ). In addition, considerable variations in geographic and sociodemographic factors (Judge, Welton, Sanhu, & Ben‐Shlomo, ; Neuburger, Hutchings, Allwood, Black, & van der Meulen, ) and indications for surgery (Dreinhofer et al, ; McBride et al, ) have been observed. Our study found out that the eHealth solution could be used to monitor referral status in real time.…”
Section: Discussionmentioning
confidence: 99%